2018
DOI: 10.1186/s12877-018-0844-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of pre-existing dementia on surgical outcomes in emergent and nonemergent general surgical procedures: assessing differences in surgical risk with dementia

Abstract: BackgroundThe aim was to assess the morbidity and in-hospital mortality that occur in surgical patients with pre-existing dementia compared with those outcomes in non-dementia patients following emergent and nonemergent general surgical operations.MethodsA total of 120 patients with dementia were matched for sex and type of surgery with 120 patients who did not have dementia, taken from a cohort of 15,295 patients undergoing surgery, in order to assess differences in surgical risk with dementia. Patient inform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 26 publications
(28 reference statements)
2
31
1
Order By: Relevance
“…Preoperative sepsis is an easily assessed preoperative factor; however, it might not be a chronic preoperative comorbidity. Similarly, previous studies also indicated that patients with preexisting dementia exhibit a high risk of early mortality after surgery, and their incidence of fatal complications was higher than that of surgical patients without dementia, although surgery was not specifically a pancreaticoduodenectomy. Patients with preoperative dementia usually show low activity and poor self‐sufficiency, which increase postoperative complications, such as surgical site infection, urinary tract infections, and respiratory complications .…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Preoperative sepsis is an easily assessed preoperative factor; however, it might not be a chronic preoperative comorbidity. Similarly, previous studies also indicated that patients with preexisting dementia exhibit a high risk of early mortality after surgery, and their incidence of fatal complications was higher than that of surgical patients without dementia, although surgery was not specifically a pancreaticoduodenectomy. Patients with preoperative dementia usually show low activity and poor self‐sufficiency, which increase postoperative complications, such as surgical site infection, urinary tract infections, and respiratory complications .…”
Section: Discussionmentioning
confidence: 73%
“…The majority of these risk factors were associated with perioperative morbidity or mortality in previous studies on pancreatic resection results . Overall morbidity after a pancreaticoduodenectomy associated with 90‐day mortality included preoperative factors that are considered risk factors for superficial and deep surgical site infection, pneumonia, unplanned intubation, renal insufficiency, and urinary tract infections . COPD is a crucial patient‐related risk factor for postoperative pulmonary complications .…”
Section: Discussionmentioning
confidence: 98%
“…44,45 Patients with mild cognitive impairment or dementia are at twofold higher risk of developing postoperative delirium as well as other adverse outcomes. 42,46 Therefore, we believe cognitive status is a critical component of any preoperative evaluation, and based on our analysis, we recommend more granular data regarding cognition be included in VQI data collection to help preoperative assessment and future quality improvement efforts.…”
Section: Discussionmentioning
confidence: 92%
“…Also in our present findings, we observed a frequent presence of dementia in the non-survivors group. It is reported that dementia is related to the incidence of surgical site infection, postoperative delirium, and pneumonia; therefore, dementia itself is considered to be one of the risk factors of surgical outcomes [27]. On the other hand, dementia is reported to be an independent risk factor for malnutrition and the odds ratio is noted to be 2.14 (p = 0.001) [28].…”
Section: Discussionmentioning
confidence: 99%